Forecast the profitability of Islamic banks in Malaysia based on Islamic interbank rate / Husnul Adib Muhamad Amin ... [et al.] - Muhamad Amin, Husnul Adib; Izani, Muhammad Alif; Ahmad Azam, Ahmad Aqil; Nordin, Muhammad Hazim; Shafie, Nur Amalina (UiTM Cawangan Negeri Sembilan, 2022)
Islamic banking is one of the trusted banking systems used in Malaysia. While the international banks have been a common staple choice around the globe, Islamic banks have risen in popularity as well as their numbers. This is due to the need of a trusted and reliable banking system which will keep their finances safe (Hachicha and Amar, 2015). The rules that govern commercial transactions in Islamic Banking are referred to as Fiqh al-muamalat. Fiqh al-muamalat can be defined as the rulings governing commercial transactions between the parties involved (Jalil et al., 2014). Islamic bank has developed ways on how to gain profit following sharia’s. Malaysia is one of the countries that have implemented the concept of Islamic finance in its banking industry. As collectively, there are 16 Islamic Banks (excluding development financial institutions) in Malaysia. Bank Negara Malaysia (BNM) acts as an organisation that administers the financial objective of the country and is following two-way banking practises: Islamic and conventional banking systems. Since Malaysia is a country, whose religion is mainly Islam, Shariah requirement must be complied with as the principle of banking operations.